Addressing social responsibility of kidney healthcare facilities in Africa - Haddiya, Intissar; Ramdani, Sara; Chtioui, Wijdane; Sidi Aly, Abdellatif; Mah, Sidi Mohamed; Niang, Abdou; Azzabi, Awatef; Elmowafy, Ahmed Yahia; Mahamat, Maimouna; Akagah Ademba, Angélique; Nzeyimana, Sylvain Pierre; Zalba, Mahamat Abderraman G. (Frontiers in Health Services, 2025)
Social responsibility (SR) in health is of paramount importance in the development of health systems. It is, therefore, frequently presented as one of the solutions for healthcare improvement in most developed countries. In addition, SR in health has been the subject of several publications in the West and Asia. However, the absence of African data on this subject motivated us to carry out this study which aimed to assess SR of African public hospitals in terms of kidney disease management, and to explore the factors that influence it based on the perceptions of patients and nephrologists, and to suggest concrete solutions to improve it.Material and methodsOur study included participants, nephrologists and patients, of public hospitals in ten African countries. Two structured questionnaires were developed to measure the perception of patients and nephrologists regarding the hospital's performance based on four dimensions: Quality of service, pertinence of care, accessibility and professional ethics. Statistical analysis of the survey data included the Student's t-test, the Chi-square test, univariate and multivariate logistic regression methods on several levels, in order to examine the factors influencing the patients’ and nephrologists’ evaluation of hospital SR.ResultsOnly 26.95% of the included patients believed that their hospitals were socially responsible. In fact, the general conditions of the hospitals and the accessibility of care (waiting times, overall cost, unavailability of treatments) were generally perceived to be unsatisfactory. Also, patients generally believed that receiving treatment regardless of their ability to pay was not always possible.As for doctors, 60% of the participants considered their hospitals not socially responsible. They had raised, in addition to the social determinants of health, a number of factors hindering SR of African hospitals, such as the lack of health professionals and brain drain.Finally, nephrologists suggested solutions, mainly directed at hospital managers, encompassing the following three components: Recruitment and training of human resources, leadership and governance, as well as strengthening of infrastructures and logistics.ConclusionOur study highlighted the crucial role of hospital governance and stakeholder involvement in improving SR and care delivery. Participants’ perceptions and concerns inform health authorities about managing kidney disease in African hospitals.